The return visit of Huarochirí or the resurrection of father Ávila - Urbano, Henrique (1982)
In recent years, several social scientists have revisited the Huarochirí region, following in the footsteps of Tello and Miranda, pioneering archaeologists from the region. In the 1950s, Matos Mar, Cotler and others studied some communities in the area and sociographically described some of their characteristics. Arguedas and Duviols, already in the 1960s, published a Spanish translation of the Huarochirí stories, together with a new paleographic edition of the Quechua manuscript. A few years later, Spalding made a historical account of the region based on archival documents. On the other hand, historians and anthropologists, such as Huertas, Duviols and Silverblatt, used the materials of the old judicial processes for idolatries to analyze some aspects of the social and religious organization of Huarochirí, comparing them with those of other Andean regions.